Rörelsemönster och golvrenhet på två olika slags spaltgolv i lösdrift för mjölkkor - Rosbacke, Carina (SLU/Dept. of Animal Environment and Health (until 231231), 2003)
About 80 % of all Swedish dairy cows are kept in tie-stalls, but loose housing is increasing, probably because it is more profitable for the farmer. The design of the floors is of cruicial importance to the cows well-being. Traditionally, the most common type of floor in the alleys of a cubicle system still is a slatted manure-draining floor made of concrete. The typical Swedish design has 125-mm slats and 40-mm slots, maximally. With too wide slots, there is an increased risk of injuries to the claws when the cow makes a hasty move. On top of that, there will be too little support for the claws, leading to injuries. A dirty floor can also increase the risk of hygiene-related diseases, mainly dermatitis and heel horn erosion, which in severe cases even may cause lameness. It has been shown earlier that by reducing the slots from 40 to 30 mm one can still achieve a good drainage. This increases the support of the claws and thus decreases the risk of traumatic injuries.